Morally ought as moral desires: A defense of internalism - Rosal, Anna Michelle Buan (Animo Repository, 2023)
Internalism asserts that there is an internal and necessary connection between our moral judgments and motivation, indicating that moral judgments motivate one to act accordingly. In contrast, Externalism posits that this connection is external and contingent, suggesting that Amoralists make sincere moral judgments without any corresponding motivation to act. This study proposes an Internalist account of moral motivation. To effectively defend Internalism against the Amoralist position, it suggests integrating a Humean framework of motivation with the concepts of moral obligation presented by Christine Korsgaard in the Sources of Normativity (1992) or Stephen Darwall in the Second-Personal Standpoint (2006). Sincere moral judgments are formed when we deliberate in a first-personal (FP) (Korsgaard) or second-personal (SP) (Darwall) perspective. As such, the motivational force is embedded in the moral judgment and comes from an internal desire to uphold the demands of morality to act as we morally should. In this regard, Amoralists do not satisfy the necessary conditions for making moral judgments in the FP or SP perspective. Even if we grant the possibility of Amoralists, it does not constitute an argument against Internalism.